Fast food bears: brown bear diet in a human‐dominated landscape with intensive supplemental feeding. Issue 1 (1st January 2015) - Kavčič, Irena; Adamič, Miha; Kaczensky, Petra; Krofel, Miha; Kobal, Milan; Jerina, Klemen
Abstract : Distribution, quantity and quality of food resources affect the diet and several other life‐history traits of large mammals. Supplemental feeding of wildlife has high potential for influencing the behaviour and diet of opportunistic omnivores, such as bears. Supplemental feeding of brown bears Ursus arctos is a common practice in several European countries, but the effects of this controversial and expensive management measure on bear diet and behaviour are poorly understood. We analysed 714 brown bear scats collected throughout the year in three regions of Slovenia with different densities of supplemental feeding sites. Supplemental food was the most important food category in the bear diet and represented 34% of the annual estimated dietary energy content (maize: 22%, livestock carrion: 12%). The proportion of supplemental food in the diet varied with season and region, being highest in spring and in the region with the highest density of feeding sites. However, considerable seasonal changes in bear diet, despite year‐round access to supplemental food, suggest that bears prefer high‐energy natural food sources, particularly insects, fruits, and hard mast, when available. Despite high availability and use of supplemental food, human—bear conflicts are frequent in Slovenia. In addition, evidence from earlier studies suggests that changes in diet and foraging behaviour due to supplemental feeding may affect several aspects of bear biology and in some cases increase the probability of human—bear conflicts. Thus, we caution against promoting unconditional supplemental feeding as a measure to prevent or reduce human—bear conflicts.